ANTI-WAR CONCEPTOLOGY IN OSYP TURIANSKYI’S REQUIEM-NOVEL “BEYOND THE LIMITS OF PAIN” - Tovt, Olga (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
Osyp Turianskyi referred to his prose work "Beyond the Limits of Pain" as a short story. However, researchers, both past and present, have assigned it various genre definitions: a memoir-novel, a poem-novel, a lyrical novel, an expressionist narrative, an anti-war novella, etc. Nevertheless, according to many Ukrainian and Western European critics, the form "requiem-novel" is perhaps the most fitting. This is because the work narrates not only the events of World War I and the horrific ordeals of its soldiers through the subjective memories of each character but also serves as a memory and a requiem for seven prisoners of war of different nationalities attempting to survive the wartime turmoil. Thus, the aim of the article is to analyze not so much the genre form of this work by the Ukrainian author but rather the system of anti-war conceptology in Osyp Turianskyi’s requiem-novel "Beyond the Limits of Pain". Consequently, the primary task for the researcher is to isolate the polyfunctionality of each concept (war, pain, death, fear, memory, recollection, life, home, family, etc.), focusing primarily on the dominant one. In the writer’s work, this is the concept of "pain". It is no coincidence that numerous researchers refer to Osyp Turianskyi’s requiem-novel as the "Book of Pain". Accordingly, the following methodological tools are proposed: comparative-historical, hermeneutic, biographical, and philological. The scientific novelty of the article lies in its examination of the Ukrainian writer’s text about World War I through the lens of conceptology, primarily through the most crucial concept of "pain" (less physical and more psychological self-expression of the heroes) that permeates the entire fabric of the artistic narrative. Therefore, the practical significance of this study is actualized by the current hardships of the Russian-Ukrainian war and numerous attempts by researchers to analyze the "vitality" embedded in the ideological and aesthetic foundations of Osyp Turianskyi’s work, as well as in the study of his artistic thinking and the clarification of his role in Ukrainian national anti-military prose in general.